BAGIAN KESRA SEBAGAI ORGANISASI SUPPORTING STAFF PENYELENGGARA KESEJAHTERAAN SOSIAL (Studi Implementasi Berdasarkan Peraturan Walikota Malang Nomor 44 Tahun 2008 tentang Uraian Tugas Pokok, Fungsi, dan Tata Kerja Sekretariat Daerah) - Dewi Citra Larasati (Universitas Tribhuwana Tunggadewi, 2012)
The complexcity of society’s problem in Malang city about social welfare give impact to the formation of Public Implementation (Kesra Division). When the government’s rules (PP) No.8 / 2003 occured. Kesra division is still called Social Division (Bagian Sosial). But after PP No.8 / 2003 was changed to PP no.41 / 2007 the nomenclature’s social division was changed becoming Kesra Division. The purpose of this study was to know and analize the implementation Kesra Division as Organization Supporting Staff Executor of Social Welfare, observed from : mechanism of work system, human resources support calculation ‘s mechanism, communication system and coordination carried out of work. Beside that, these study also try to identified the problem that’s faced by Kesra Division. Base on the research that is conducted is obtained the result that is 1) statment of tupoksi that it’s used Malang Mayor are multi interpretation. So, it’s not changed will arouse overlapping with other SKPD whereas in fact of works’ machanism showed of Kesra Division as Supporting Staff organization of that is organized of social welfare that stay on the level of “PREVENTIVE” and “REHABILITATION/SOCIAL AID”.